Determination Of Plasma Metabolites, Its Related Metabolomic Pathways And Correlation With Clinical Parameters Of Cognitive Frailty And Mild Cognitive Impairment - Bawadikji, Abdulkader Ahmad (2023)
Cognitive frailty (CF) has evolved over recent years, initially used to describe the co-occurrence of mild cognitive impairment (MCI) and physical frailty without dementia. Population ageing is occurring globally, and Malaysia has the most rapidly growing older population. CF in old age is likely to become of increasing importance. Metabolomics is a novel scientific discipline that may provide a novel method for diagnosing CF using a sensitive and specific technique such as nuclear magnetic resonance (NMR). This study aims to identify metabolic fingerprints that can be used to distinguish subjects with CF from MCI and robust (healthy group), to explore the pathway of the identified metabolites, and to explore the correlations between the identified biomarkers and the clinical data related to CF and MCI. Blood samples were collected from 56 CF (mean age: 72.6 years), 75 MCI (mean age: 65.1 years), and 78 robust (mean age: 63.3 years). Plasma was separated by centrifugation, and then plasma samples were mixed with phosphate buffer and analyzed using NMR spectroscopy. Data analysis was done using multivariate analysis, including principal component analysis (PCA) and partial least square discriminate analysis (PLS-DA). For discrimination between CF and robust, the PLS-DA model showed sensitivity, specificity, and accuracy of 66.1%, 67.9%, and 65%, respectively.